RETRACTED ARTICLE: User Experience–Driven Design of a Digital Bamboo Weaving Interface for Intangible Cultural Heritage Preservation - ICRP Editorial Office (Journal of Intercultural Communication, 2025)
The Publisher [1] has retracted this article in agreement with the Editor-in-Chief. Upon investigation, it was found that the submission involved fraudulent practices, and concerns were raised regarding the contributions of the authors of the article. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: (1) Human AI conent or irrelevant content included in the article (2) Discrepancies in the description of the research reported (3) Discrepancies between the availability of data and the research described (4) Peer-review manipulation Following an internal investigation conducted in accordance with ICR Publications’ Research Integrity, Authorship, and Publication Ethics Policies, the Editorial Office has confirmed a serious breach of authorship policies and publication ethics. Accordingly, this article is hereby retracted. This notice is issued solely to inform readers that the content of the article is unreliable. At this stage, we have not determined whether the authors were aware of, or involved in, any systematic manipulation of the publication or peer-review process. ICR Publications and the Journal of Intercultural Communication (JICC) regret that these issues were not identified during the standard quality-control procedures. We have since implemented additional editorial safeguards and strengthened verification checks to ensure the highest standards of research integrity. The corresponding author, acting on behalf of all listed authors, was given the opportunity to state their agreement or disagreement with this retraction. We have kept a formal record of all responses received. This retraction is issued in accordance with the COPE Retraction Guidelines and forms part of ICR Publications’ commitment to maintaining the accuracy and integrity of the scholarly record. The original article can be found online at https://doi.org/10.36923/jicc.vi.1204